(untitled) (Global Journal of Human-Social Science, 2014)
There have long been conflicting expectations of the nature of companies responsibilities to society Some businesses have been practising what might be termed Corporate Social Responsibility CSR focusing on corporate image management or other activities aimed predominantly at business benefits This paper discusses why corporate social responsibility is no longer an option for business organisations nor is still about programmes to produce socially and environmentally friendly products A new paradigm in corporate social responsibility for corporations in developing countries is presented in which they need to create a strategic partnership with supply chain members support their strategic partners and understand the effect of their bought-in products on the society as a whole